Fractal analysis of fractograms of aluminum alloys irradiated with high current electron beam - Donets, S.Ye.; Lytvynenko, V.V.; Startsev, O.A.; Lonin, Yu.F.; Ponomarev, A.G.; Uvarov, V.T. (Physics and Chemistry of Solid State, 2023)
The aluminum alloys D16 and AMg6 were irradiated using the high-current relativistic electron beam in vacuum. Intense electron irradiation of the materials modified their physical properties. The fractal character of the fracture surfaces’ images was studied. The change of the fractality is a distinguished descriptor of the materials modification. The characteristic ductile and brittle fractures are accompanied by the change of the fractal dimension.